Assessing Strength of Pelvic Floor Muscle in Pelvic Organ Prolapse - Shrestha, Sabina; Shrestha, Madhu; Dangal, Ganesh; Shrestha, Alka (Birat Journal of Health Sciences, 2024)
Introduction: Pelvic organ prolapse (POP) is a debilitating condition affecting around 75% of women of different age group and parity. Reduced pelvic floor muscle strength in POP is associated with worse symptoms and prognosis.Objectives: To assess the pelvic floor muscle strength in pelvic organ prolapse of different stagesMethodology: This cross sectional study included women with pelvic organ prolapse attending outpatient department of Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu. The clinical examination included the pelvic organ prolapse quantification (POP-Q)-system examination and Modified Oxford Scale. Statistical analysis included Pearson’s correlation (p